Free WiFi to monitor flow in Hanoian traditional markets - Reymondin, Louis; Le Trung, Hieu; Vantalon, Thibaud; Pham, Huong; Phan, Trong; Nguyen, Kien (2021)
Despite being the main source of fresh, convenient, and affordable food for 80% of Hanoi’s population, food flows within traditional markets remain largely invisible due to a lack of tracing systems and environmental conditions which make traditional tracking approaches challenging.